PELATIHAN PENULISAN SITASI DALAM ARTIKEL ILMIAH DENGAN APLIKASI MENDELEY PADA MAHASISWA POLITEKNIK LP3I JAKARTA - Handayani, Puspita; Nurhayati, Nurhayati; Silviyani, Yuli Anita (Fokus ABDIMAS, 2023)
Mendeley is one of the mandatory applications for students, especially for students who are writing scientific articles, journals, or theses. In writing scientific papers, students are often faced with an obstacle in proper writing formats and scientific references. Citations are an important element in writing a scientific paper. The existence of software, such as Mendeley that can be used to help write citations, allows authors to properly cite their reference documents. On the other hand, the bibliography is also closely related to a scientific paper. Citations used in the paper should be contained in the bibliography and vice versa. In order to build students' knowledge of the importance of citation of scientific papers and to build proficiency in using the Mendeley application, our PKM team wants to teach students to understand the benefits of the Mendeley application in writing citations and bibliography of scientific papers. Based on the activities that have been carried out, participants are able to make citations and bibliography in scientific papers using the help of the Medeley application properly and within a short peripd of time. Proper and neat citations and bibliography will help students of Politeknik LP3I Jakarta – Pondok Cabe Campus to complete their final projects. Keywords: Citations, scientific papers, mendeley